Aplikasi Editor Pemeriksa Ejaan dan Rekomendasi Kata dalam Bahasa Indonesia Berbasis Android - Dwi, Febria Roosita; Intan, Rolly; Santoso, Leo Willyanto (Jurnal Infra, 2016)
Indonesian has now become more popular internationally, for example, Vietnam used Indonesian Bahasa as their second language. There are several ways to helping people to learn Indonesian Bahasa, one of them is by creating a tool that allows them to determine whether the language the are currently learning is true or not. This thesis discusses the application of Indonesian editor with spell checker and diction recommendation features in IndonesianThe process is carried out as follows: users opens a file or typing in the editor, words input will be checked with Apache Lucene, and Lucene will crawling to all of the data and give the recommendation base on the weight (Leveinsthein Algorithm) and if a user opens a file, the application will perform spell checking using Nazief and Adriani algoritm. The result of this process is the result of input that is underlined words that is not in accordance with Indonesian, or suitable recommendation result by Apache Lucene. Input could be words or .doc file. As Output will be written in .doc file and the spell checking results and words recommendation will be shown in editor as the user types. This application is built using Java programming language and Android Studio as the IDE.The test result shows that the accuracy of the Nazief and Adriani Algorthms still need to be improved, word length and word complexity also affects the time in the checking process, for example: to check documents with 100 words, there are various of time from 1.48 minutes to 3.3 minutes. Besides that, this algoritm can not check the word which had 2 syllables, like âpertanggungjawabanâ because of the stemming process.